Psychometric Properties of the Acoso Sexual en las Instituciones de Educación Superior Scale (ASIES) in an Ecuadorian Sample - Guarderas-Albuja, Paz (2023)
Sexual harassment has become increasingly common in Ecuador’s higher education centers. However, due to the lack of instruments that evaluate sexual harassment, the magnitude of this phenomenon in Ecuador is unknown. This research aims to analyze the construct validity and internal consistency reliability of a sexual harassment measurement scale in higher education institutions (ASIES). The instrument analyzes 21 behaviors related to sexual harassment. The sample consisted of 4628 people. A descriptive analysis of the items, item-total correlation analysis, and both exploratory and confirmatory factor analysis are performed to test the internal structure of the scale. It was found that the 4-factor model and a second-order factor presented a better fit (CFI = .99, TLI = .99, SRMR = .075, and RMSEA =.018). The results confirm the four dimensions proposed.